The Role of Sports Tourism In Improving The Economy of Local Communities of Natural Tourism Objects (Rafting) In Oloboju Village, Sigi Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the role of sports tourism, particularly whitewater rafting, in improving the local economy in Oloboju Village, Sigi Regency. The research method used a quantitative approach with a survey technique through the distribution of questionnaires to 15 respondents consisting of tourism managers and business people around the tourist attraction. Data were analyzed using descriptive percentage techniques. The results showed that the majority of the community assessed the economic impact of whitewater rafting tourism in the categories of "Sufficient" (47%), "Good" (33%), "Poor" (13%), and "Very Poor" (7%). No respondents rated it in the category of "Very Good". These findings indicate that whitewater rafting tourism has the potential to improve community welfare, but is still hampered by limited infrastructure, low promotion, minimal community participation, and less than optimal support from the local government. This study recommends development strategies in the form of local community empowerment, infrastructure improvement, digital promotion, diversification of tourist attractions, and collaboration between stakeholders.